Enhancement of Sensing Performance for Alcohol in Aqueous Solution Using Tapered Optical Fiber Coated with Polyaniline Via Air-Brushing Technique - Noor Aliah Kahlet; Mat Isa, Naimah; Sakinah Mohd Alauddin; Norhafizah Burham; Hasnida Saad (International Journal of Integrated Engineering, 2024)
Tapered fibers with superior properties can be used in sensing applications such as humidity sensors, temperature sensors, and refractive index sensors. The main objective of this work is to investigate the influence of Polyaniline (PANI) as a coating in the fabrication of a polymer microfiber for the detection of different concentrations of methanol, ethanol, and propanol. In this study, a high-quality tapered optical fiber is fabricated using the flame-brushing technique and the microfiber is then coated with the polymer Polyaniline (PANI) to detect different types of alcohol at various concentrations. It was found that the sensor using PANI as the coating material on the tapered optical fiber exhibited higher sensitivity to concentration changes of aliphatic alcohol solutions than the bare tapered optical fiber. The improvement in sensitivity for methanol, ethanol, and propanol is 80.17%, 106.43%, and 42.92% respectively. A sensitivity of 0.9755 dBm/%, 1.06 dBm/%, and 1.039 dBm/% for methanol, ethanol, and propanol respectively was achieved by using a tapered PANI-coated optical fiber with a diameter and length of 4 µm and 5 mm respectively. The digital microscope (DM) confirmed the successful coating of PANI on the tapered microfiber which helped to enhance the performance of the sensor. Overall, this work has effectively demonstrated a conductive polymer-coated optical microfiber sensor for alcohol detection that is inexpensive, effective, and easy to set up.